2019
DOI: 10.1177/0363546519865529
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Results of Arthroscopic Rotator Cuff Repair: Initial Tear Size Matters: A Prospective Study on Clinical and Radiological Results at a Minimum Follow-up of 10 Years

Abstract: Background: Arthroscopic techniques are now considered the gold standard for treatment of most rotator cuff (RC) tears; however, no consensus exists on the maintenance of results over time, and long-term follow-up data have been reported for few cohorts of patients. Purpose: To present the long-term results associated with the arthroscopic treatment of RC tears and to evaluate associations between preoperative factors and RC integrity at final follow-up. Study Design: Cohort study; Level of evidence, 3. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 53 publications
1
36
0
Order By: Relevance
“…When conservative therapy is ineffective, open or arthroscopic surgery using suture anchors in a variety of configurations is used with the goal of reducing pain and increasing function [11]. Despite traditional management with surgery to repair partial and full-thickness rotator cuff tears, several studies have shown high failure rates of tendon to bone rotator cuff repairs ranging from 30% to 94% [1,2,11,12]. It can be difficult to determine which types and sizes of tears will benefit from surgical management as tear size and morphology have been shown to be poor predictors for pain and functional scores [13].…”
Section: Introductionmentioning
confidence: 99%
“…When conservative therapy is ineffective, open or arthroscopic surgery using suture anchors in a variety of configurations is used with the goal of reducing pain and increasing function [11]. Despite traditional management with surgery to repair partial and full-thickness rotator cuff tears, several studies have shown high failure rates of tendon to bone rotator cuff repairs ranging from 30% to 94% [1,2,11,12]. It can be difficult to determine which types and sizes of tears will benefit from surgical management as tear size and morphology have been shown to be poor predictors for pain and functional scores [13].…”
Section: Introductionmentioning
confidence: 99%
“…Two such studies have reported recurrent tears after arthroscopic SR repair in approximately 50% and 52% of patients. 10,28 Repair failures were further associated with functional impairment and progressive osteoarthritic changes. 9,16,28 To our knowledge, no studies have investigated long-term results after DR repair techniques.…”
mentioning
confidence: 99%
“…Randelli recently reported 10 year results after arthroscopic cuff repair, including complete follow-up of 102 out of 169 patients (60 %) 231 . Despite a retear rate of 51 %, the mean Constant score was 78 for the whole cohort, 81 for small tears (< 2 cm) and 70 for larger tears.…”
Section: Acromioplasty Without Cuff Repairmentioning
confidence: 99%
“…Three additional studies with long-term results 53,120,231 have been published after this review. Radiographic results 20 years after rotator cuff repair was published recently by HervĂ© et al and a frequency of 29 % osteoarthritis was reported 120 , but their definition of osteoarthritis did not include Hamada grade 2 and 3.…”
Section: Acromioplasty Without Cuff Repairmentioning
confidence: 99%